Substrate stiffness modulates cardiac fibroblast activation, senescence, and proinflammatory secretory phenotype - Felisbino, Marina B; Rubino, Marcello; Travers, Joshua G; Schuetze, Katherine B; Lemieux, Madeleine E; Anseth, Kristi S; Aguado, Brian A; McKinsey, Timothy A (American journal of physiology. Heart and circulatory physiology, 2024)
In vitro cultures of primary cardiac fibroblasts (CFs), the major extracellular matrix (ECM)-producing cells of the heart, are used to determine molecular mechanisms of cardiac fibrosis. However, the supraphysiologic stiffness of tissue culture polystyrene (TCPS) triggers the conversion of CFs into an activated myofibroblast-like state, and serial passage of the cells results in the induction of replicative senescence. These phenotypic switches confound the interpretation of experimental data obtained with cultured CFs. In an attempt to circumvent TCPS-induced activation and senescence of CFs, we used poly(ethylene glycol) (PEG) hydrogels as cell culture platforms with low and high stiffness formulations to mimic healthy and fibrotic hearts, respectively. Low hydrogel stiffness converted activated CFs into a quiescent state with a reduced abundance of α-smooth muscle actin (α-SMA)-containing stress fibers. Unexpectedly, lower substrate stiffness concomitantly augmented CF senescence, marked by elevated senescence-associated β-galactosidase (SA-β-Gal) activity and increased expression of p16 and p21, which are antiproliferative markers of senescence. Using dynamically stiffening hydrogels with phototunable cross-linking capabilities, we demonstrate that premature, substrate-induced CF senescence is partially reversible. RNA-sequencing analysis revealed widespread transcriptional reprogramming of CFs cultured on low-stiffness hydrogels, with a reduction in the expression of profibrotic genes encoding ECM proteins, and an attendant increase in expression of NF-κB-responsive inflammatory genes that typify the senescence-associated secretory phenotype (SASP). Our findings demonstrate that alterations in matrix stiffness profoundly impact CF cell state transitions, and suggest mechanisms by which CFs change phenotype in vivo depending on the stiffness of the myocardial microenvironment in which they reside. Our findings highlight the advantages and pitfalls associated with culturing cardiac fibroblasts on hydrogels of varying stiffness. The findings also define stiffness-dependent signaling and transcriptional networks in cardiac fibroblasts.